Amino Acid Supplementation in Fish Nutrition and Welfare - Cláudia Aragão; Sofia Engrola; Benjamín Costas (Animals)
Amino acids are not only the fundamental building blocks of proteins and, consequently, essential for animal growth, but they have also gained recognition in recent years for their critical roles in regulating key metabolic processes [...]